2021
DOI: 10.3991/ijet.v16i06.18847
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Using Google Classroom to Support the Learning Processes in the Automation and Programming Course

Abstract: Virtual and blended learning are suggested as means to support students’ learning of the subject matter. The present study sought to examine how one educational tool for the classroom; specifically Google Classroom, was used by a teacher of automation and programming course in the secondary school. One secondary school teacher and her two students participated in the re-search. The data collection tools were interviews of two types: asking the participants semi-structured questions, and requesting the teacher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…As a result, it is clear that the preservice teacher experienced a new teaching methodology successfully (Baya'a, Daher & Anabousy, 2019;Daher, 2015), here the STEM methodology, which points out the importance of professional development programs that expose teachers to new methodologies and technologies (Abuzant, Ghanem, Abd-Rabo & Daher, 2021;Anabousy & Tabach, 2019;Daher, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it is clear that the preservice teacher experienced a new teaching methodology successfully (Baya'a, Daher & Anabousy, 2019;Daher, 2015), here the STEM methodology, which points out the importance of professional development programs that expose teachers to new methodologies and technologies (Abuzant, Ghanem, Abd-Rabo & Daher, 2021;Anabousy & Tabach, 2019;Daher, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Google Classroom is free and has many facilitating features to support distance learning, its usage has been massive during the pandemic period where face to face activities at school have shifted to distance models. Many studies relating to the use of Google Classroom as the web-based platform in the pandemic of covid 19 period have been conducted and resulted in positive findings, especially about the perceptions of the users [36]- [38]. The benefits of using Google Classroom during covid 19 pandemic based on teachers' view were usefulness, ease of use, friendliness to environment (paperless usage), satisfaction in process, and outcome satisfaction [10].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This concern of the principals with tools potentiality for quality education mean that this quality is assumed by the principals to be one potentiality of technological tools. Abuzant et al [38] found that distance learning platforms, specifically Google Classroom, could serve as a quality learning environment. In addition, quality education could be achieved through electronic manipulatives, as they facilitate the problem solving done by students [39].…”
Section: Use Of Technological Tools To Achieve Quality Educationmentioning
confidence: 99%